Redesigning Technical Vocational Education and Training for Sustainable Economic Development in Nigeria - Nzube Muogahlu; Adnan Bin Ahmad (Journal of Vocational Education Studies, 2023)
Nigeria adopted TVET programs in her education strategy to educate and train qualified workers and develop middle-level personnel who will be self-sufficient to grow the economy and national stability. Nigeria's economy and national cohesion are threatened by various concerns. The country's problems include high unemployment, deep poverty, and increased insecurity. Nigeria's TVET program must be redesigned to develop 21st-century workers to stabilize and build the economy to avoid these challenges. This study aimed at redesigning TVET for sustainable economic development through the provision of skilled and competent work force for industries and for self-reliant. The study took a review method where secondary data were uncovered through reviewing of variety of literatures, newspapers, National reports, policy documents, national data etc. A possible explanation for the country's part of continued economic instability and low levels of productivity, unstable GDP growth, and high rate of unemployment can be traced to poor quality of TVET. Findings from the review of empirical literature discovered lack of employable skills, inadequate technical skills, and the incapacity of TVET graduates to compete in the global workplace. All these findings necessitated the redesigning of TVET in the following regards: updating the curriculum, TVET institutions partnership with industries, adopting a new model of programme operation, adequate funding and teachers’ training. Recommendations such as government in collaboration with private sectors and Multinational companies to invest more in human capital through education, mainly TVET, remains the key to sustainable economic development in Nigeria.